Student Rental Apartment with Green Architecture Application in Medan City (International Journal of Architecture and Urbanism, 2022)
Medan city has become the economic, political, educational, and socio-cultural center in North Sumatra Province. Medan has a variety of religions, cultures, and tribes. The development of education, especially universities, makes Medan one of the goals for students who have completed their education at the high school level. The college will bring students from out of town and within the city. In addition, clothing and residential food become one of the needs of students. Students from out of town will need temporary housing that can be rented during their college education. Accommodation must be tailored to the needs and culture of students. The apartment has become one of the alternative housing for students. Green Architecture is one of the alternatives in designing buildings, where this concept can minimize damage to the environment and building users. The application of energy-saving to structures will positively impact users of the building and the building itself.